Analysis Of Waiting Time For Patient Services Of Disease Polyclinic At Hkbp Balige General Hospital - Fitri Yanti; Andi Josep; Viki Nora Wati Sijabat (International Journal of Health Engineering and Technology, 2023)
Waiting time for prescription services is a minimum standard for pharmaceutical services, with fast waiting times it can improve the quality of pharmaceutical services. The waiting time for non-concoction or concoction prescription services is the time period from when the patient submits the prescription to receiving non-concoction or concoction drugs with a length of time ≤ 30 minutes for non-concoction drugs and ≤ 60 minutes. This study aims to determine the waiting time for prescription services at the Outpatient Internal Medicine Polyclinic at HKBP Balige General Hospital. The design used in this study was descriptive, the population was all outpatient prescriptions at the Internal Medicine Polyclinic. The research sample was 80 recipes taken by accidental sampling. The instrument used is the prescription service waiting time observation sheet. Based on data analysis, 16 recipes (20%) met the requirements and 64 recipes (80%) did not meet the requirements and were non-concoction recipes. The results of this study indicate that the waiting time for prescription services is not up to standard. It is hoped that the management of the HKBP General Hospital will add Pharmacy Technical Personnel to the Pharmacy Installation so that the waiting time for prescription services will be faster.